Memória e ficção: as publicações literárias do jornal Diário da Tarde - Ilhéus, como construto de memória da Região do Cacau - Barreto, Antonio Valter Santos (2018)
The present thesis chooses as object of investigation the literary texts published in the newspaper Diário da Tarde de Ilhéus, in the years 1929, 1931, 1933, 1935 and how these, at the same time, construct and represent the memory of the society of Ilhéus and region of cacao, which comprises the south and part of the southern tip of the State of Bahia, in the field of literature, religion, history and memories. The newspaper can be seen as a place or archive of memory, because in its publications it is possible to interpret facts and events of the first half of the twentieth century, be they literary, religious or cultural, since journalistic support can also be seen as a guardian of facts and events, that is, presents and represents, at the same time, a memory guarded, archived, sacralized in its vestiges. Since memory is that which stores, records and represents facts and events of the past, it is open to the dialectic of remembrance and oblivion. For this, studies on memory and forgetfulness were based on theorists such as Maurice Halbwchs (2006), Paolo Rossi (2010), Janice Theodoro (1998), on file and place of memory from the conceptions of Pierre Nora (1993), Foucault (2002), Elisabeth Roudinesco (2006), Derrida (2001), as well as how about the press, the novel and the use of the pseudonym, something very frequent in the literary news published in Diário da Tarde, Socorro of Fatima (2007), Myrian Sepúlveda (2003) and Marlyse Meyer (1996). The concepts of these and other theorists were debated with the purpose of inserting the ilheense newspaper in this archive of representations and place of memory in the service of an elite, a people and a region considered rich and place of colonels, at the same time maintained considerable literary production with publications in the newspaper support.